Application of a Sub-set of Skinfold Sites for Ultrasound Measurement of Subcutaneous Adiposity and Percentage Body Fat Estimation in Athletes - O’Neill, D. C.; Cronin, O.; O’Neill, S. B.; Woods, T.; Keohane, D. M.; Molloy, M. G.; Falvey, E. C. (International Journal of Sports Medicine, 2016)
Body composition assessment is an integral feature of elite sport as optimization facilitates successful performance. This study aims to refine the use of B-mode ultrasound in the assessment of athlete body composition by determining suitable sites for measurement. 67 elite athletes recruited from the Human Performance Laboratory, University College Cork, Ireland, underwent dual measurement of body composition. Subcutaneous adipose tissue thickness at 7 anatomical sites were measured using ultrasound and compared to percentage body fat values determined using Dual-Energy X-ray Absorptiometry. Multiple linear regressions were performed and an equation to predict percentage body fat was derived. The present study found subcutaneous adipose tissue depths at the triceps, biceps, anterior thigh and supraspinale sites correlated significantly with percentage body fat by X-ray absorptiometry (all p<0.05). Summation of the depths at these locations correlated strongly with percentage body fat by Dual-Energy X-ray Absorptiometry (R²=0.879). The triceps, biceps, anterior thigh and supraspinale sites are suitable anatomical landmarks for the estimation of %BF using B-mode ultrasound. Use of B-mode ultrasound in the assessment of athlete body composition confers many benefits including lack of ionising radiation and its potential to be used as a portable field tool.
Keywords: absorptiometry; sports; ultrasound imaging